Volume Estimation of the Thickest Scoriaceous Tephra-Fall Deposits on the South-Southeastern Flank of Mt. Raung - Wibowo, Haryo Edi; Harijoko, Agung; Cahyani, Sherinna Mega; Moktikanana, Mradipta Lintang Alifcanta; Prawira Sari, Shafa Hadaina (Journal of Applied Geology, 2023)
Thick scoriaceous tephra-fall deposits are widely distributed in the south to the southeast flank of Mt. Raung, indicating the existence of past large explosive eruptions. The deposits are relatively young as the deposits are situated near the surface. Scoriaceous tephra-fall deposits can be divided into four layers from bottom to top, Scoria Fall 1, Scoria Fall 2, Scoria Fall 3, and Scoria Fall 4. There is no time gap between these layers, as evidenced by the deposits not being separated by any weathered layer or soil, suggesting that the deposits represent an eruptive product of a single active period. We estimated the volume of the deposits using isopach maps following Weibull method to identify the magnitude of the eruption. We limited the estimation only to Scoria Fall 2 and Scoria Fall 3 deposits which were consistently exposed on 13 and 9 observation points, respectively. The volume of Scoria Fall 2 is ~0.54 km3 and Scoria Fall 3 is ~0.26 km3 making the total volume of 0.8 km3 (VEI 4).